Protektorátní. Kalendář paní a dívek českých jako pokus zachovat prostor pro „veřejnou“ ženu - Libuše Heczková (Slovo a Smysl)
This study focuses on the activities of the Women’s Centre at the Czech National Council during the years 1938–1945. Using the example of its activities, and in particular the publication Calendar of Czech Ladies and Girls, it shows how the strategy of women’s public action gradually changed in a period that was hostile to women, when laws and norms were strengthened that obliged women to serve their country only through their procreative function, pushing women into the domestic sphere or into forced labour.